2016
DOI: 10.5430/ijhe.v5n2p283
|View full text |Cite
|
Sign up to set email alerts
|

Geography Teachers’ Attitudes and Beliefs Regarding Classroom Management

Abstract: This study scrutinizes geography teachers' attitude and belief levels regarding classroom management. As a matter of fact, classroom management is one of the prominent areas emphasized by all educators. Descriptive correlational survey model was used in the study. Study group includes 58 geography teachers working in Sivas province during the 2015-2016 academic year. Convenience sampling method was employed while forming the study group. The Attitudes & Beliefs on Classroom Control Inventory developed by Marti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…On the contrary, [25] indicated no significant difference between teachers' belief levels in classroom management by the type of the high school they worked in. Similarly, [26] argued that there is no difference in efficacies between different types of schools when demographic factors are held constant.…”
Section: Literature Reviewmentioning
confidence: 72%
See 1 more Smart Citation
“…On the contrary, [25] indicated no significant difference between teachers' belief levels in classroom management by the type of the high school they worked in. Similarly, [26] argued that there is no difference in efficacies between different types of schools when demographic factors are held constant.…”
Section: Literature Reviewmentioning
confidence: 72%
“…Different types of school have different teaching-learning conditions, characterized by class sizes and provision of facilities [26]. In agreement, [25] revealed that there was no statistically significant difference between teachers' mean scores for student engagement by the type of the high school. In Kenya, secondary schools are categorized as Sub-County, County or National schools.…”
Section: Literature Reviewmentioning
confidence: 77%
“…There are a number of studies concerning classroom management practices both in traditional (face-to-face) learning and online learning (see, for example, Adeyemo, 2012;Anwar et al, 2020;Cho et al, 2020;Cristina, 2020;Dustova & Cotton, 2014;Hoang et al, 2020;Lasari, 2021;Milliken, 2019;Oliver et al, 2011;Sammaknejad & Marzban, 2016;Setyani, 2021;Soleimani & Razmjoo, 2019;Wut & Xu, 2021). The findings have led to the widespread conclusion that effective classroom management is critical for successful teacher-student interactions and negotiations (Anwar et al, 2020;Dikmenli & Çifçi, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In relation to this, scholars have recently explored how classroom management is geared by teachers (see, for example, Egeberg, Mcconney, & Price, 2016;Eisenman, Edwards, & Cushman, 2015;George, Sakirudeen, & Sunday, 2017;Jalali & Panahzade, 2014;Kubat, 2018;Liu & Babchuk, 2018;Selcuk, Kadi, Yildirim, & Celebi, 2017). The results have informed uniform findings that classroom management is essential for teacher-student interactions and negotiations (Dikmenli & Çifç, 2016).…”
Section: Introductionmentioning
confidence: 99%